One More Evidence Supporting Damage Growth Inside Silicon MEMS Structures from Comparison of Strength Affected by Cyclic Compressive Stress - Vu Le Huy (Lecture Notes in Mechanical Engineering, 2021)
Recently, dislocation in single-crystal silicon has been confirmed to be induced by fatigue. It was found that the fatigue lifetime of silicon is likely to be dominated by accumulation of crystal defects, i.e., dislocations. In previous studies, crystal d